2009
DOI: 10.1177/0003319709351875
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease as a Predictor of Coronary Lesion Morphology

Abstract: Coronary artery disease (CAD) is the main cause of death in patients with chronic kidney disease (CKD). We investigated whether CKD stage affected coronary lesion morphology in patients with established CAD. Coronary angiograms of 264 patients were evaluated. Chronic kidney disease was staged using the estimated glomerular filtration rate (eGFR) from the serum creatinine prior to coronary angiography. Patients were divided into 3 groups: dialysis or severe decrease in GFR <30 mL/min per 1.73 m(2) (group 1; n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(43 reference statements)
0
14
0
1
Order By: Relevance
“…Finally, an association between mor-tality and vitamin D deficiency has been shown in dialysis-and nondialysis-dependent CKD (7,11). Because the risk of cardiovascular disease is higher in CKD than non-CKD patients, the potential benefits of vitamin D supplementation (from here on this refers to vitamin D2-ergocalciferol or D3-cholecalciferol supplementation) may be greater in CKD than non-CKD individuals (12).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an association between mor-tality and vitamin D deficiency has been shown in dialysis-and nondialysis-dependent CKD (7,11). Because the risk of cardiovascular disease is higher in CKD than non-CKD patients, the potential benefits of vitamin D supplementation (from here on this refers to vitamin D2-ergocalciferol or D3-cholecalciferol supplementation) may be greater in CKD than non-CKD individuals (12).…”
Section: Introductionmentioning
confidence: 99%
“…The association between CKD and CAD has been investigated for a number of years. Kilickesmez et al (33) demonstrated that CKD has an independent influence on lesion morphology and complexity. Abaci et al (34) concluded that the eGFR was an independent predictor of the extension and severity of CAD among patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] A strong relationship between severe renal dysfunction, and extent and complexity of coronary artery disease (CAD) has been investigated in only a few previous studies. [5][6][7] It has been demonstrated that even a slight decrease in the GFR poses an independent risk factor for cardiovascular diseases. [8] However, this association was not investigated in patients with stable CAD and normal to mildly impaired renal function.…”
mentioning
confidence: 99%